2017
DOI: 10.1038/s41598-017-05816-w
|View full text |Cite
|
Sign up to set email alerts
|

Loss of type 9 adenylyl cyclase triggers reduced phosphorylation of Hsp20 and diastolic dysfunction

Abstract: Adenylyl cyclase type 9 (AC9) is found tightly associated with the scaffolding protein Yotiao and the IKs ion channel in heart. But apart from potential IKs regulation, physiological roles for AC9 are unknown. We show that loss of AC9 in mice reduces less than 3% of total AC activity in heart but eliminates Yotiao-associated AC activity. AC9−/− mice exhibit no structural abnormalities but show a significant bradycardia, consistent with AC9 expression in sinoatrial node. Global changes in PKA phosphorylation pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(61 citation statements)
references
References 55 publications
5
56
0
Order By: Relevance
“…Genetic deletion of AC9 is mostly embryonic lethal [6,41,42], but a small fraction of AC9 null homozygotes survive [42,43]. Examination of the cardiac function of these animals [43] showed that the cAMP-dependent phosphorylation of the heat-shock protein Hsp20 is compromised, raising the possibility that AC9 in the heart may have a cardioprotective role [44]. Taken together, switching of the responsiveness of AC9 via proteolysis in the C2b domain may determine the spectrum of intracellular cAMP effectors activated in a complex extracellular stimulus environment such as that seen in neuronal development or myocardial hypertrophy.…”
Section: Limited Proteolysis and Ac9mentioning
confidence: 99%
“…Genetic deletion of AC9 is mostly embryonic lethal [6,41,42], but a small fraction of AC9 null homozygotes survive [42,43]. Examination of the cardiac function of these animals [43] showed that the cAMP-dependent phosphorylation of the heat-shock protein Hsp20 is compromised, raising the possibility that AC9 in the heart may have a cardioprotective role [44]. Taken together, switching of the responsiveness of AC9 via proteolysis in the C2b domain may determine the spectrum of intracellular cAMP effectors activated in a complex extracellular stimulus environment such as that seen in neuronal development or myocardial hypertrophy.…”
Section: Limited Proteolysis and Ac9mentioning
confidence: 99%
“…Of the AC isoforms, AC9 is the most divergent in sequence and the most understudied. Expression analysis shows that AC9 is widely expressed in the central nervous system, heart, and other tissues (Premont et al, 1996;Paterson et al, 2000;Sosunov et al, 2001;Berndt et al, 2013;Li et al, 2017). Although AC9 knockout mice were initially reported to be embryonically lethal (Antoni, 2006), mice lacking AC9 protein expression are viable despite a preweaning subviable homozygous phenotype with incomplete penetrance (Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Expression analysis shows that AC9 is widely expressed in the central nervous system, heart, and other tissues (Premont et al, 1996;Paterson et al, 2000;Sosunov et al, 2001;Berndt et al, 2013;Li et al, 2017). Although AC9 knockout mice were initially reported to be embryonically lethal (Antoni, 2006), mice lacking AC9 protein expression are viable despite a preweaning subviable homozygous phenotype with incomplete penetrance (Li et al, 2017). Knockdown and gene-trapping studies provide clear in vivo roles for AC9 in neutrophil chemotaxis (Liu et al, 2010(Liu et al, , 2014 and cardiac function (Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations